Preferable university by matriculation students using Analytical Hierarchy Process (AHP) / Wardina Syafiah Mohd Fadzil, Nurul Falah Mohd Razali and Nurul Huda Shahrudin - Mohd Fadzil, Wardina Syafiah; Mohd Razali, Nurul Falah; Shahrudin, Nurul Huda (2023)
The idea of attending a university to study is exciting to many students. They will experience a new environment, meet new people, and gain new knowledge. However, students must be aware of their options for higher education study and comprehend their options for study pathways before they apply to a university. Choosing the right path is very important for students, and it will be a difficult process if the students are unprepared. Matriculation students lack a structured application to assist them in planning their degree based on certain factors. Hence, poor preparation and knowledge about degree planning will lead to confusion among students due to the variety of higher-level institution options available to a student. To overcome this problem, this research will identify the factors that influence students’ decisions to attend higher education institutions using the Analytical Hierarchy Process (AHP). It is also will determine the preferred institutions that students in this cohort pick and examine the nature of the connection between the institutions that students prefer; and the selection criteria that influence their decisions. This study deals with the application of the Analytical Hierarchy Process (AHP) for determining the preferred university by matriculation students. The main sample for this study was drawn from Melaka's Matriculation College students over the age of 18. The data is gathered by analyzing the preferred university selection process and includes the identification of relevant criteria that are found necessary by students, such as college fees, friends and family influence, career path availability, course availability, the location of institutions, and scholarship coverage. The finding reveals that most students chose a public institution (IPTA) based on the availability of required courses and programs. This study is expected to be significant for professionals, higher education institution managements, and future researchers.